2020
DOI: 10.3390/ijms21124567
|View full text |Cite
|
Sign up to set email alerts
|

Binding of CML-Modified as Well as Heat-Glycated β-lactoglobulin to Receptors for AGEs Is Determined by Charge and Hydrophobicity

Abstract: Intake of dietary advanced glycation end products (AGEs) is associated with inflammation-related health problems. Nε-carboxymethyl lysine (CML) is one of the best characterised AGEs in processed food. AGEs have been described as ligands for receptors present on antigen presenting cells. However, changes in protein secondary and tertiary structure also induce binding to AGE receptors. We aimed to discriminate the role of different protein modifications in binding to AGE receptors. Therefore, β-lactoglobulin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 55 publications
(76 reference statements)
0
21
0
Order By: Relevance
“…The involvement of both hydrophobicity and exposure of -sheet structures -next to or in combination with glycation of food proteins -in binding to AGE receptors has also recently been demonstrated in other studies. [20,36] Although, for non-fractionated BLG, heating seemed to be a driving force for binding to the receptors, the aggregates isolated from BLG-Glu showed enhanced binding and uptake by THP-1 cells compared to the aggregates isolated from BLG-H and BLG-Lac. This indicates that glycation of BLG, especially with glucose, also plays a role in the generation of specific binding ligands for receptors present on APCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of both hydrophobicity and exposure of -sheet structures -next to or in combination with glycation of food proteins -in binding to AGE receptors has also recently been demonstrated in other studies. [20,36] Although, for non-fractionated BLG, heating seemed to be a driving force for binding to the receptors, the aggregates isolated from BLG-Glu showed enhanced binding and uptake by THP-1 cells compared to the aggregates isolated from BLG-H and BLG-Lac. This indicates that glycation of BLG, especially with glucose, also plays a role in the generation of specific binding ligands for receptors present on APCs.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of both hydrophobicity and exposure of β‐sheet structures ‐ next to or in combination with glycation of food proteins ‐ in binding to AGE receptors has also recently been demonstrated in other studies. [ 20,36 ]…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggested that diets with high AGE content can also result in higher uptake of AGE-modified peptides. As recently shown, the binding of AGE receptors depends on the concentration of food protein bound AGEs [22]. Therefore, quantitative data would be necessary to better judge the impact of the transport of AGE-modified peptides on the gastrointestinal immune system as well as the involved transport pathways.…”
Section: Identification Of Peptides On the Basolateral Side Of The Camentioning
confidence: 99%
“…Moreover, the generation of peptides carrying a glycation structure can modulate the inflammatory response by binding to the receptors for AGEs on antigen presenting cells [14,20]. Binding of AGEs to AGE receptors has particularly been shown for protein-bound CML and pyrroline [21,22], while for peptide bound AGEs this was only demonstrated for CML [20]. The availability of AGE-modified peptides to the gastrointestinal immune system by means of translocation across the epithelial barrier is an important determinant in the immunological response to a foreign antigen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation